On penal metrics - Tremblay, Pierre (Journal of quantitative criminology, 1988)
This paper presents the results of a public survey on the perceived severity of different kinds and levels of penalties gathered using magnitude estimation techniques. Three topics are dealt with. Individual scales of sentence severity are shown to be internally consistent. Then the structural properties of the severity scales of fine, imprisonment, community work, and probation are analyzed. Finally, what a given penalty is worth in relation to other types of punishment from the public's point of view is established and compared to existing exchange rates prescribed in legal statutues or practiced by criminal courts.